Determinants of Taxpayer Compliance: An Integrative Approach - Awaludin; Ronny Andesto (Jurnal Akuntansi, 2026)
This study investigates the effects of tax rate policy, the implementation of PMK 66/2023, and tax sanctions on taxpayer compliance, with tax socialization as a moderating variable. Tax compliance plays a critical role in sustaining state revenue, making it essential to assess the effectiveness of regulatory policies and tax education. Using a quantitative survey approach, data were collected from individual taxpayers registered at KPP Pratama Jakarta Kelapa Gading. A total of 140 respondents were selected through simple random sampling. The data were analyzed using multiple regression and Moderated Regression Analysis (MRA) supported by SMARTPLS 3.2.9. The findings reveal that tax rate policy does not significantly affect taxpayer compliance, whereas the implementation of PMK 66/2023 and tax sanctions positively and significantly influence compliance. The moderating analysis shows that tax socialization strengthens the effects of tax rate policy and PMK 66/2023 but weakens the relationship between tax sanctions and taxpayer compliance.